Two new species of Crocicreas (Helotiaceae, Ascomycota) revealed by morphological and molecular data - Zheng, Huan-Di; Zhuang, Wen-Ying (Phytotaxa, 2016)
Two new species of Crocicreas are established based on morphological features and DNA sequence data. Crocicreas luteolum is distinct by combination of the following features: caulicolous, hymenium surface yellow, margin plane, ectal excipulum of textura prismatica, asci J+, 62−81 × 6.0−7.7 µm, and ascospores fusoid, biguttulate, 11−14 × 2.2−3.3 µm. Crocicreas pseudobambusae is featured by combination of bambusicolous, hymenium surface white to beige, margin plane, ectal excipulum of textura intricata, asci J+, 36−58 × 3.5−5.5 µm, and ascospores ellipsoid, eguttulate, 4.5−7.7 × 1.8−2.5 µm. Description, illustration and comparison with related fungi are provided for each species. Sequence analyses of the internal transcribed spacer of nuclear ribosomal DNA are used to confirm their generic positions.